Off Track: The Disappearance of Tracking Stocks. Issue 4 (December 2014) - Davidson, Travis; Harper, Joel
<x xml:space="preserve">Abstract</x> During the two decades following the first announcement of a tracking stock issue by General Motors in 1984, over 50 new tracking stocks were created. The value of a tracking stock is supposed to reflect the performance of a division or operation of a firm, but does not have a direct claim on the division's assets or income. The voting rights of the tracking stock are only for the parent corporation, with no direct voting rights for the tracked division. The claimed benefits of issuing tracking stock include the use of internal capital markets, additional disclosure of the firm's operations, reduction of agency costs, the ability to directly compensate divisional management on performance, and greater analyst following and liquidity. But the last new issue of a tracking stock took place in 2001. And few, if any, tracking stocks still trade. This study examines how and why tracking stocks have largely stopped being issued, and why so many have been dissolved either through exchanges of shares, or sales or spin‐offs of the business units with tracking stock.